2019
DOI: 10.1007/s10388-019-00660-5
|View full text |Cite
|
Sign up to set email alerts
|

Host factors influence Barrett’s carcinogenesis: findings from a mouse gastroduodenal reflux model

Abstract: Background Rat gastroduodenal reflux models have been used for analyzing Barrett’s carcinogenesis. Mice seem to be more useful than rats for studies targeting genes. Methods We induced gastroduodenal contents reflux by esophagojejunostomy using C57BL/6J mice. Mice were divided into a standard diet and high-fat diet groups and kept for 60 weeks. Bile was sampled from the gallbladder to analyze bile acid fractions, and the esophagus was removed for a histological investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…Eleven studies examined the effect of BAs on proliferation (51,60,62,(66)(67)(68)(72)(73)(74)(75)(76)(77)(78), see Table 4. Four were human studies (60,62,66,77) and seven were carried out in human cell-lines (68,(72)(73)(74)(75)(76)78). Two studies were carried out on non-malignant oesophageal cells (66,72), four were carried out on BO (60,62,73,77) and five on OAC (68,(74)(75)(76)78).…”
Section: Publications Relating To Cell Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…Eleven studies examined the effect of BAs on proliferation (51,60,62,(66)(67)(68)(72)(73)(74)(75)(76)(77)(78), see Table 4. Four were human studies (60,62,66,77) and seven were carried out in human cell-lines (68,(72)(73)(74)(75)(76)78). Two studies were carried out on non-malignant oesophageal cells (66,72), four were carried out on BO (60,62,73,77) and five on OAC (68,(74)(75)(76)78).…”
Section: Publications Relating To Cell Proliferationmentioning
confidence: 99%
“…Eleven studies examined the effect of BAs on proliferation (51,60,62,(66)(67)(68)(72)(73)(74)(75)(76)(77)(78), see Table 4. Four were human studies (60,62,66,77) and seven were carried out in human cell-lines (68,(72)(73)(74)(75)(76)78).…”
Section: Publications Relating To Cell Proliferationmentioning
confidence: 99%
See 1 more Smart Citation
“…Chronic exposure of the esophageal mucosa to gastroduodenal fluid (bile salts and hydrochloric acid) causes active and erosive esophagitis, resulting in metaplasia of squamous cells to columnar epithelial cells, and submucosal fibrosis as Barrett's esophagus. It has been shown that chronic gastroesophageal reflux induces Barrett's esophagus according to clinicopathological analyses [5,6] and experimental studies using animal models [7][8][9][10]. Regarding the requirement of goblet cells (intestinal metaplasia) within the columnar-lined mucosa, the global histological definition of Barrett's esophagus is still controversial in Europe, the US, the UK and Japan [5] (Figure 2).…”
Section: Gerd-barrett's Esophagus (Mucosal Remodeling)-adenocarcinomamentioning
confidence: 99%
“…We selected taurocholic acid (TCA) among various bile acids to stimulate ESCC cells because of the following 5 reasons: (i) in cases with Barrett's esophagus/stricture, taurine conjugates are predominant in the esophagus; (ii) increased proportions of taurine conjugates due to a high‐fat diet influence Barrett's carcinogenesis in reflux models; (iii) exposure to TCA promotes cell proliferation in a dose‐dependent manner in an experiment using E‐G junction cancer cells (OE‐19); (iv) chronic exposure to TCA causes tumor progression in ESCC cells; and (v) acid and bile acids induce NF‐κB pathway signaling in esophageal squamous cells in gastroesophageal reflux disease . In addition, TCA significantly increased protein levels of p‐NF‐κB (p65) in both a time‐dependent and dose‐dependent manner, and TCA significantly increased nuclear translocation of NF‐κB (p65) in a human cholangiocarcinoma cell line…”
Section: Introductionmentioning
confidence: 99%